Innovative Prototype development for Concrete Sales Management of Saha Nakhonpathom Concrete Co., Ltd - Kullayapichet, Chanitpak; Rakbumrung, Wilailuk (Journal of Innovation and Management, 2020)
The objectives of this research study were to (1) contrast individual degrees of acceptance of the innovative prototype for sales management of concrete, sorted by the demographic characteristics and (2) investigate the technological factors that influence the acceptance of the innovative prototype for the sales management of concrete. The research is conducted in a quantitative design. The samples of the study were selected by the systematic sampling, comprised of 400 customers of the company. Questionnaires were employed. The collected data were analyzed by means of (1) descriptive statistics: frequency, percentage, average, and standard deviation and (2) inferential statistics: ANOVA and multiple regression analysis. The Research Findings were as follows: (1) Concerned with the demographic characteristics of the participants (gender, age, education, and current profession), it has been disclosed that the participating customers with different professions were reported showing differences in accepting the innovative prototype for the sales management of concrete, which is at a level of .05. For the other factors, the difference was not found, and (2) Regarding the technological acceptance, it has been revealed that the perceived ease of use, perceived usefulness, attitude toward using as well as behavioral intention to use could have decent influence on the individuals. Such factors could present approximately 65% of acceptance tendency. Then, after the test of independent and dependent variables, it has been found that merely two factors (perceived usefulness and behavioral intention to use) could influence the individuals to accept the innovative prototype for the sales management of concrete, significantly at a statistical level of .05.